INFLUÊNCIA DA MATÉRIA ORGÂNICA NA ADSORÇÃO DE Hg E OUTROS ELEMENTOS EM SEDIMENTOS DE LAGOS DA BACIA DO RIO MADEIRA (RO) - Vergotti, M.; Bonotto, D. M.; Silveira, E. G.; Bastos, W. R. (Geochimica Brasiliensis, 2012)